The Effect of Tax Knowledge and Taxpayer Awareness on Taxpayer Compliance - Margaret, Eveline; Damayanti, Fera; Rusliyawati, Rusliyawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to examine the influence of tax knowledge, tax awareness, and tax sanctions on the compliance of Individual Taxpayers. The research uses a quantitative method with accidental sampling technique, involving 81 respondents who are Individual Taxpayers. Data was collected through questionnaires and analyzed using IBM SPSS Statistics 22 with a significance level of 5% or 0.05. The results show that tax knowledge does not have a positive effect on taxpayer compliance. This is due to the low level of tax knowledge among taxpayers, which reduces their motivation to fulfill tax obligations. On the other hand, tax awareness and tax sanctions have a positive effect on compliance. High awareness of the importance of taxes and the effective enforcement of sanctions are driving factors for taxpayers to be more compliant in fulfilling their obligations. This study highlights the importance of improving tax literacy and enforcing sanctions to enhance tax compliance rates.